Desenvolvimento de sistemas biométicos para detecção de bumetanida e hidroclorotiazida em amostras de interesse farmacêutico e biológico - Ruy, Mayara Regina dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work is based on the construction of biomimetic sensors for sensitive and selective determination of diuretics for bumetanide (BMT) and hydrochlorothiazide (HCTZ). Carbon paste-based electrodes were modified with complexes, which are potential biomimetic catalysts of P450 enzymes, that catalyze a number of reactions including pharmaceuticals. The complexes Copper (II) 1,2,3,4,8,9,10, 11,15,16,17,18,22,23,24,25-hexadecafluoro-29-H,31-H-phthalocyanine [CuPc] and Hemin showed biomimetic profile and better results for amperometric and voltammetric determination of bumetanide and hidroclorotiziada, respectively. The experimental conditions for the proposed methodologies development have been optimized with the help of design of multivariate experiments. The sensor built to determine the diuretic bumetanide presented the best responses in Britton-Robinson buffer 0.15 mol L-1 pH 7.0 and 15 % (m/m) of the complex [CuPc], using the square wave voltammetry with 60 Hz, amplitude of potential of 100 mV and step potencial of 6 mV. With the optimized parameters the sensor showed limits of detection and quantification of 0.27 and 0.9 μmol L-1,respectively. The best results for the sensor have been developed for hydrochlorothiazide phosphate solution 0.10 mol L-1 pH 8.5 and 14 % (m/m) of the hemin, using the amperometry at 800 mV, limits of detection and quantification of 8.2 and 27 μmol L-1, respectively. Studies conducted for elucidation of sensor biomimetic behavior, such as evaluation of scan rate influence using cyclic voltammetry, exploration of hyperbolic profile of the sensor response, interference and selectivity studies. In a complementary, a molecular imprinting polymer, known as MIP, was developed for bumetanide. The MIPs were synthesized by bulk polymerization. Studies were based on the results obtained from the computer simulation where monomer of high structural affinity, acrylonitrile...

O presente trabalho está baseado na construção de sensores biomiméticos para determinação sensível e seletiva dos diuréticos: bumetanida (BMT) e hidroclorotiazida (HCTZ). Para isto, eletrodos à base de pasta de carbono foram modificados com complexos, os quais são potenciais catalisadores biomiméticos das enzimas P450, que catalisam um grande número de reações incluindo os fármacos. Os complexos que apresentaram perfil biomimético e melhores resultados na determinação voltamétrica e amperométrica da bumetanida e hidroclorotiziada, respectivamente foram 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro 29-H, 31-H-ftalocianinacobre (II) [CuPc] e hemina. As condições experimentais para o desenvolvimento das metodologias propostas foram otimizadas com auxílio de planejamento de experimentos multivariados. O sensor construído para determinação do diurético bumetanida apresentou as melhores respostas em solução tampão Britton-Robinson 0,15 mol L-1 pH 7,0 e 15% m/m do complexo [CuPc], usando a voltametria de onda quadrada a 60 Hz, 100 mV de amplitude e 6 mV de incremento de potencial (Δps). Com os parâmetros otimizados, o sensor apresentou limites de detecção e de quantificação de 0,27 e 0,9 μmol L-1, respectivamente. Os melhores resultados obtidos para o sensor desenvolvido para a hidroclorotiazida foram em solução fosfato 0,10 mol L-1 pH 8,5 e 14% m/m de hemina usando a amperometria em 800 mV, e os limites de detecção e de quantificação de 8,2 e 27 μmol L-1, respectivamente. Avaliou-se também a biomimeticidade do sensor, explorando o perfil hiperbólico da resposta nos sensores, velocidade de varredura e estudo de interferentes. Os sensores foram satisfatoriamente usados nas análises em amostras de interesse farmacêutico e biológico, assim se apresentam com alternativas vantajosas em relação a outros métodos disponíveis, pois apresentam baixo custo...
Keywords: Diureticos; Biomimetismo; Analise eletroquimica; Dopagem em esportes; Polímeros